Development of nanotechnologies for curd dessеrts and fruit and vegetable cryo-additives for their preparation as bas enrichers, structure-forming agents, and colorants - Pavlyuk, Raisa; Pogarskaya, Viktoriya; Balabai, Ekateryna; Pogarskiy, Aleksey; Stukonozhenko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports the newly devised method and nanotechnology for production of curd desserts for healthy nutrition. They include the mechanical processing of curd grains accompanied by processes of mechanical activation and non-enzymatic catalysis of the casein-calcium-phosphate complex into a nanoscale form, as an innovation. The nanotechnology of cryo-additives made from fruits and vegetables has been devised. We used them as fortifiers with biologically active substances (BAS), natural structure formers and colorants in curd desserts. New curd desserts have the nanoscale form and possess a high content of natural BAS of fruits and vegetables (β-carotene, phenolic compounds, tannins, chlorophylls, L-ascorbic acid and soluble pectin substances). The latter serve as natural fortifiers and structure formers in curd desserts. The above makes it possible to eliminate a need to use food additives and synthetic additives. The low-fat curds were used as a base for production of curd desserts for healthy nutrition. We selected the following raw materials for production of fruit and vegetable cryo-additives: carotene-containing fruits (pumpkin, apricots, and sea buckthorn), citruses (lemons with rind), Jerusalem artichokes, spinach, and apples. We considered homogenization of a product as a technological approach, which leads not only to obtaining of a homogeneous structure of a product, but also to processes of mechanical activation, mechanical destruction and mechanolysis, which is destruction of a protein to its individual components. An increase in the mass fraction of free α-amino acids and simple peptides occurs during the mentioned processes. The study showed that 40...45 % of the bound α-amino acids of protein transform into a free, easily digestible form. The size of α-amino acid molecules is from 0.3 to 1.5 nm. We revealed the mechanism of the process associated with the mechanocracking of protein and its components with mineral substances in the study. The fillers in the form of cryopaste made of fruits and vegetables for curd desserts have been prepared. They are the source of a unique complex of natural biologically active substances, namely, phytocomponents, such as phenolic compounds (1...2.1 %), carotenoids (32.6...45.6 mg per 100 g), L-ascorbic acid (102...260 mg per 100 g), and chlorophylls (800...1,680 mg per 100 g). We showed that fruit and vegetable cryopastes exceed raw materials by 2.5...3.5 times in the content of biologically active substances, due to extraction of hidden forms of BAS from raw materials. In addition, they have a high content of soluble pectic substances due to extraction of hidden inactive forms into a free form from fresh raw materials when preparing paste-like cryofillers. We developed formulations and technology for curd desserts and studied the content of BAS. Curd desserts exceed the known analogues by chemical composition.